Change Management: Blended Learning Adoption in a Large Network of European Universities - Dion, Guillaume; Stoycheva, Milena; Tejero, Alberto; Vendel, Martin; Dalle, Jean-Michel; Renouard, Frédéric; Guseva, Yulia; León, Gonzalo; Marchese, Maurizio; Mutanen, Olli-Pekka; Stranger, Alvaro Pina; Pisoni, Galena (Proceedings of the International Conference on e-Learning (Online), 2018)
We report in this paper on a multiyear endeavour within the EIT (European Institute of Innovation and Technology) Digital community, during which EIT Digital built an international community of Innovation and Entrepreneurship ("I&E") teachers at Master level by implementing a blended learning strategy. We see this challenge as a case in change management, which could offer relevant insight to run similar initiatives of blending learning adoption as an enabler to developing pedagogical cooperation in networks of universities with real impact on practices. Through the lenses of change management theory, we describe and analyse the methods that allowed EIT Digital to create and enhance a community of "teacher-producers" in order to develop and deploy blended education from scratch. EIT Digital, a Knowledge and Innovation Community of the European Institute of Innovation and Technology (EIT), provides IT education at Master's level since 2013 and in association with its around 20 member universities, including a strong "Innovation & Entrepreneurship" ("I&E") education component. EIT Digital developed a blended learning strategy whose originality came from the fact that some of the teachers are also producers on behalf of the entire community, receiving associated co-funding and technical support from EIT Digital. More specifically, teachers actively took part to the production agenda, according to which producers were chosen within the community to create and deliver the agreed online contents. EIT Digital library now encompasses more than 500 basic online contents ("nuggets") covering most topics relevant for I&E education at the graduate level, from basic business model introductions to complex technology transfer strategies. This amounts to more than 45 hours' worth of videos along with dozens of written cases, quizzes and other forms of online/offline assignments. Depending on the various universities' contexts, different blending strategies were deployed, which had practical consequences on the global EIT Digital development. The heterogeneity of the universities' profiles probably significantly increased the value of the EIT Digital network which proved relevant with regards to blended learning adoption, while EIT Digital's change management strategy contributed significantly to uplifting the I&E education offered at the member universities, notably giving momentum to its I&E teacher community.